Effect of Body Mass Index on Left Ventricular Mass in Career Male Firefighters - Korre, Maria; Porto, Luiz Guilherme Grossi; Farioli, Andrea; Yang, Justin; Christiani, David C.; Christophi, Costas A.; Lombardi, David A.; Kovacs, Richard J.; Mastouri, Ronald; Abbasi, Siddique A.; Steigner, Michael L.; Moffatt, Steven M.; et al. (My University, 2016)
Left ventricular (LV) mass is a strong predictor of cardiovascular disease (CVD) events; increased LV mass is common among US firefighters and plays a major role in firefighter sudden cardiac death. We aim to identify significant predictors of LV mass among firefighters. Cross-sectional study of 400 career male firefighters selected by an enriched randomization strategy. Weighted analyses were performed based on the total number of risk factors per subject with inverse probability weighting. LV mass was assessed by echocardiography (ECHO) and cardiac magnetic resonance, and normalized (indexed) for height. CVD risk parameters included vital signs at rest, body mass index (BMI)–defined obesity, obstructive sleep apnea risk, low cardiorespiratory fitness, and physical activity. Linear regression models were performed. In multivariate analyses, BMI was the only consistent significant independent predictor of LV mass indexes (all, p <0.001). A 1-unit decrease in BMI was associated with 1-unit (g/m1.7) reduction of LV mass/height1.7 after adjustment for age, obstructive sleep apnea risk, and cardiorespiratory fitness. In conclusion, after height-indexing ECHO-measured and cardiac magnetic resonance–measured LV mass, BMI was found to be a major driver of LV mass among firefighters. Our findings taken together with previous research suggest that reducing obesity will improve CVD risk profiles and decrease on-duty CVD and sudden cardiac death events in the fire service. Our results may also support targeted noninvasive screening for LV hypertrophy with ECHO among obese firefighters.
Keywords: Left ventricular mass; Cardiovascular disease; Cardiac death